IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS AJARAN AL-QUR’AN DAN HADIS SERTA DAMPAKNYA BAGI PESERTA DIDIK DI MTs. AL-ISHLAH KABUPATEN BANDUNG JAWA BARAT - Rihanah, Dewi Fitria Angraeni (UNISAN JURNAL, 2024)
This research examines the implementation of character education based on the teachings of the Al-Qur’an and Hadith at MTs. Al-Ishlah and its impact on students. Through a holistic approach, the program successfully shapes students’ characters with strong Islamic values, enhances their spirituality, and strengthens interpersonal relationships within the school. Using qualitative methods, data were collected through observation, interviews, and document analysis. The results show that the implementation of character education has a positive impact, helping students understand and internalize Islamic teachings in their daily lives. The program also produces students with noble character traits who are ready to face societal challenges. Thus, character education based on the teachings of the Al-Qur’an and Hadith at MTs. Al-Ishlah plays a crucial role in shaping a generation with noble character and high competitiveness. This research contributes to a better understanding of the importance of character education in the context of Islamic education. Keywords: Character Education, Al Qur’an and Hadith